Physicochemical, rheological and digestibility characterization of starch extracted from the marine green macroalga Ulva ohnoi. (November 2021) - Kazir, Meital; Gurevich, Daniel; Groobman, Ari; Prabhu, Meghanath; Israel, Álvaro; Golberg, Alexander; Livney, Yoav D.
Abstract: Edible green marine macroalgae, especially species of Ulva, can accumulate starch up to 30% of their dry weight; however, its physicochemical, functional, and digestibility properties are still unknown. In this study, we characterized molecular mass distribution, amylose-amylopectin ratio, crystallinity, hydration capacity, viscoelastic and pasting properties, and the digestibility of starch extracted from Ulva ohnoi and compared it to rice and potato starches. Ulva starch had a higher amylose content than rice and potato starches (55.0%, 34.5% and 24.3%, respectively). Ulva starch exhibited higher hydration capacity than rice starch (25.7 gwater /gstarch and 10.3 gwater /gstarch respectively), while potato starch exhibited the highest hydration capacity, of 41 gwater /gstarch, probably mainly due to presence of phosphate groups. Ulva starch had the lowest mass-average molecular weight ((1.17×10 6  g/mol), compared to rice (4.40×10 6  g/mol) and potato (5.80×10 6  g/mol) starches. Ulva starch exhibited the highest G′ and viscosity setback ratio after cooling-induced gelation following gelatinization, probably thanks to its uniquely high amylose content, which led to higher tendency for physical crosslinking by retrogradation. This may also explain the fact that Ulva starch exhibited somewhat lower digestibility after retrogradation, compared to rice and potato starches, which would be advantageous for forming resistant starch serving as a dietary fiber, and lowering glycemic index. The superior gel properties on the one hand and lower digestibility, which would be helpful in tackling obesity & diabetes, on the other hand, make U lva starch a unique and promising new functional food ingredient. Graphical abstract: Image 1 Highlights: Ulva ohnoi amylose content: 55% of the starch, more than most terrestrial starches. Ulva starch exhibited higher hydration capacity than rice starch. Gelatinized Ulva starch exhibited the highest G′ after cooling-induced gelation. Ulva starch had somewhat lower digestibility than rice and potato starches. Lower digestibility may lead to lower glycemic index, advantageous against diabetes.